1985
DOI: 10.1063/1.95887
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast carrier and grating lifetimes in semiconductor-doped glasses

Abstract: The time dependence of both the photoluminescence due to carrier recombination and the gratings created by degenerate four-wave mixing were measured in semiconductor-doped color-filter glasses. Values ranging from 80 to less than 16 ps (laser pulse width limited) are measured in several different samples at various excitation levels. A slower mechanism, believed to be thermal in nature, is also observed with a lifetime in excess of 9 ns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(29 citation statements)
references
References 1 publication
1
25
1
Order By: Relevance
“…Yao et al 1) and Tomita et al 2) observed fast response; however, we did not. This may be due to the detrapping effect and the low time resolution of the experimental apparatus.…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…Yao et al 1) and Tomita et al 2) observed fast response; however, we did not. This may be due to the detrapping effect and the low time resolution of the experimental apparatus.…”
contrasting
confidence: 53%
“…This may be due to the detrapping effect and the low time resolution of the experimental apparatus. The extremely fast response reported by Yao et al 1) is probably due to a photodarkening effect. 4) In summary, time-resolved luminescence spectra of CdS-doped glass are reported.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…It is perhaps the simplest generalization of the ubiquitous Kerr law and models a material whose refractive index depends on the optical field amplitude raised to a power other than 2. Various semiconductors, for example InSb [19] and GaAs/GaAlAs [20], doped filter glasses (such as CdS x Se 1-x ) [21], and liquid crystals (such as MBBA) [18], can possess power-law behaviour in their refractive index. Power-law solitary waves have been investigated theoretically in the context of interface surface modes [22], and as elementary excitations in thin films [23] and slab waveguides [24].…”
mentioning
confidence: 99%
“…1). With all three input pulses coincident on than 16 p, ilaser pulse width limitedi, the sample, a reflection efficiency of 1% at f1 MW/cm 2 The photoluminescence measurements were made uspump power was observed. This signal level is slightly lower ing a mode-locked train of pulses of 30-ps duration and 50-than that previously reported in Ref.…”
Section: -mentioning
confidence: 99%